Shortened cycles of use in commercial property — a problem for urban planning? - Bunzel, Arno; Henckel, Dietrich (Raumforschung und Raumordnung | Spatial Research and Planning, 2003)
Against the background of legislative considerations to introduce a temporary building law, the article considers the question whether shortened cycles of use really exist for commercial property and which possibilities to control them would be available. In contrast to generally accepted theses there is largely no empirical evidence to determine whether and to what extent shortened cycles of use exist and which dimension these shortened cycles of use have in temporal and quantitative terms (the extent to which locations and branches are affected). It is true that there are a number of plausible clues that indicate a shortening of cycles of use in parts of the commercial property market. Generally legal and economic policy options are already available for such cases today. Complementary legal instruments are only required for a few special cases, otherwise there is merely a need for helpful measures that support the existing set of instruments.